Upaya Pendidikan Agama Islam dalam Menangkal Radikalisme - Fadhil Akbar (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Islamic education is one of the institutions that came into the spotlight when inter-religious and ethnic riots emerged in several places in Indonesia. Education is felt to be extra necessary to provide sufficient provisions to students on how they develop a tolerant attitude towards differences and diversity that exist in society. Awareness of the urgency of pluralism and inclusive (open) education design is expected to be able to play an educational function that is able to form friendly people and empathize with the anxiety of every human being without exception, including those who are non-Muslims. Then what kind of understanding of PAI values should be strengthened in an effort to counteract the flow of radicalism?